Investigation on the Phalange Contact Force for a 2 finger Pulley-Tendon Driven Robotic Hand - Mahmoud, Ali Moghavvemi (IRC, 2016)
The loss of a limb gives an enormous social, psychological and economic impact to the amputee. Replacement of an absent limb with an artificial limb, which may restore some functionality, is very expensive and a very complex process. Today, such technologies exist but it comes at a very high cost with unsatisfactory tracking ability. The anatomy of the human hand and its actuators were investigated to determine the effect of actuator force, object radius and joint spring stiffness on the contact force of the finger phalanges. It is found that, actuator force is directly proportional to the contact forces of the phalanges, object radius reduces the contact force as radius increases and spring stiffness will reduce the contact force of the phalanges. Spring stiffness if designed correctly, tends to average out the contact force of the phalanges, resulting in a more stable grasp. To take this project further, more optimization options need to be explored to output a more accurate result and apply the same method to add more fingers, ultimately resembling a human hand.